2014
DOI: 10.1016/j.urolonc.2013.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Complications associated with single-dose, perioperative mitomycin-C for patients undergoing bladder tumor resection

Abstract: OBJECTIVES To better understand the risk of short-term complications associated with perioperative intravesical mitomycin-C (MMC) therapy for patients undergoing endoscopic management of non-muscle invasive bladder cancer (NMIBC). METHODS AND MATERIALS Using an institutional database of patients with bladder cancer, we performed a retrospective case-control study of patients receiving perioperative MMC after tumor resection (2008–2012). MMC cases were matched by clinical stage to controls receiving endoscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Along with TUR, intravesical therapy is the mainstay of therapy/prevention for NMIBC. Single‐dose postoperative chemotherapy has been shown to reduce the risk of recurrence , however, 67% of urologists in a national US sample never administer immediate postoperative therapy owing to lack of chemotherapy availability, expense, tumour depth/perforation uncertainty, or fear of toxic side effects . Recent results published by the SWOG group showed that single‐dose postoperative intravesical gemcitabine reduces recurrence by 20% in histologically confirmed low‐grade NMIBC at a median follow‐up of 4 years in a randomized prospective sample .…”
Section: Resultsmentioning
confidence: 99%
“…Along with TUR, intravesical therapy is the mainstay of therapy/prevention for NMIBC. Single‐dose postoperative chemotherapy has been shown to reduce the risk of recurrence , however, 67% of urologists in a national US sample never administer immediate postoperative therapy owing to lack of chemotherapy availability, expense, tumour depth/perforation uncertainty, or fear of toxic side effects . Recent results published by the SWOG group showed that single‐dose postoperative intravesical gemcitabine reduces recurrence by 20% in histologically confirmed low‐grade NMIBC at a median follow‐up of 4 years in a randomized prospective sample .…”
Section: Resultsmentioning
confidence: 99%
“…Mitomycin C is the most common cytotoxic drug used to treat bladder cancer and has been shown to reduce the risk of recurrence (Bosschieter et al, 2018). Although it is an effective intravesical treatment, mitomycin C (MMC) is known to cause urological side effects in 34.5%-41% of patients who undergo treatment, the most common being increased urinary frequency and urgency, and painful urination (Thrasher and Crawford, 1992;Filson et al, 2014). Other side effects include pelvic pain and hematuria.…”
Section: Introductionmentioning
confidence: 99%
“…The most regular complication following even a single dosage of MMC is aseptic cystitis, present as urinary urgency, frequency and dysuria. 11 Vanni et al, 14 with their study showed 72% success in 18 patients managed with deep cold-knife incision subsequently with MMC injection. Triamcinolone acetonide as well as MMC lowers scar proliferation.…”
Section: Discussionmentioning
confidence: 97%